The Influence of Principal Leadership and Teacher Career Development on Teacher Performance at MAN 2 Pati in 2025 - Sulistiono, Sulistiono; Fitri Wulandari (Penerbit Presisi Pustaka, 2026)
Teacher performance is a crucial factor in improving the quality of education, necessitating effective principal leadership and sustainable career development. At MAN 2 Pati, the demand for improved learning quality by 2025 necessitates an evaluation of the influence of these two factors. The purpose of this study was to determine the partial influence of principal leadership and teacher career development on teacher performance, as well as the simultaneous influence of principal leadership and teacher career development on teacher performance. The research method used was a quantitative correlational method. Data were collected using a questionnaire, which had been tested for validity and reliability. Prior to the correlation analysis, the data were subjected to prerequisite analysis tests, including normality, linearity, multicollinearity, and heteroscedasticity. Furthermore, product-moment correlation analysis (partial correlation) and multiple correlation analysis were performed. The study population consisted of 75 students, with a saturated sampling technique, so all members of the population were included as respondents. The results showed that principal leadership significantly influenced teacher performance at MAN 2 Pati in 2025, as indicated by a significance value of 0.044 <0.05 with a contribution of 14%. Teacher career development also significantly influenced teacher performance at MAN 2 Pati in 2025, with a significance value of 0.000 <0.05 and a contribution of 43%. Furthermore, both variables, principal leadership and teacher career development, simultaneously influenced teacher performance at MAN 2 Pati in 2025, with a significance value of 0.01 <0.05, and an F-count of 29.838, greater than F-table of 2.7318, and a contribution of 43%. These findings underscore the importance of strong principal leadership and structured career development programs in improving the quality of education.